Built-In Electric Field-Driven Ultrahigh-Rate K-Ion Storage via Heterostructure Engineering of Dual Tellurides Integrated with Ti3C2Tx MXene - Pan, Long; Hu, Rongxiang; Zhang, Yuan; Sha, Dawei; Cao, Xin; Li, Zhuoran; Zhao, Yonggui; Ding, Jiangxiang; Wang, Yaping; Sun, ZhengMing (Nano-Micro Letters, 2023)
Exploiting high-rate anode materials with fast K+ diffusion is intriguing for the development of advanced potassium-ion batteries (KIBs) but remains unrealized. Here, heterostructure engineering is proposed to construct the dual transition metal tellurides (CoTe2/ZnTe), which are anchored onto two-dimensional (2D) Ti3C2Tx MXene nanosheets. Various theoretical modeling and experimental findings reveal that heterostructure engineering can regulate the electronic structures of CoTe2/ZnTe interfaces, improving K+ diffusion and adsorption. In addition, the different work functions between CoTe2/ZnTe induce a robust built-in electric field at the CoTe2/ZnTe interface, providing a strong driving force to facilitate charge transport. Moreover, the conductive and elastic Ti3C2Tx can effectively promote electrode conductivity and alleviate the volume change of CoTe2/ZnTe heterostructures upon cycling. Owing to these merits, the resulting CoTe2/ZnTe/Ti3C2Tx (CZT) exhibit excellent rate capability (137.0 mAh g−1 at 10 A g−1) and cycling stability (175.3 mAh g−1 after 4000 cycles at 3.0 A g−1, with a high capacity retention of 89.4%). More impressively, the CZT-based full cells demonstrate high energy density (220.2 Wh kg−1) and power density (837.2 W kg−1). This work provides a general and effective strategy by integrating heterostructure engineering and 2D material nanocompositing for designing advanced high-rate anode materials for next-generation KIBs. Highlights: 1 Heterostructure engineering is proposed to construct CoTe2/ZnTe heterostructures with built-in electric field. 2 Conductive and elastic Ti3C2Tx MXene is introduced to improve the conductivity and alleviate the volume change of CoTe2/ZnTe upon cycling. 3 The resulting CoTe2/ZnTe/Ti3C2Tx (CZT) demonstrates outstanding rate capability (137.0 mAh g−1 at 10 A g−1) and cycling stability (175.3 mAh g−1 after 4000 cycles at 3.0 A g−1). Moreover, the CZT-based full cells demonstrate excellent energy density (220.2 Wh kg−1) and power density (837.2 W kg−1).